HALAL TOURISM ON MANDAILING NATAL IS HAMPERED DUE TO THE COVID-19 PANDEMIC - Siti Holidah; Munawir Pasaribu (Proceeding International Seminar of Islamic Studies, 2021)
: Halal tourism is a tourism that really prioritizes the elements of halalness in several aspects related to tourism activities. Halal also includes everything that is used for the human body and mind which of course is free from danger. Halal in general includes: property, food, drinks, cosmetics, medicines, materials and handling of diseases or life problems. Halal has become a global issue at this time, including in Indonesia. At the state level, Indonesia is set to become a global halal center. Halal is clearly visible by the Ministry of Tourism which seeks to increase the number of tourists visiting Indonesia, especially those visiting halal tourism. Several regions are trying to compete to become areas that are friendly to halal tourism, such as Mandailing Natal. The current trend of halal tourism is necessary to know the concepts and parameters used in carrying out halal tourism. The data collection method uses the documentary method based on primary and secondary literature reviews. This study aims to conduct an in-depth analysis of the concept of halal tourism and several parameters that are used as standards for halal tourist destinations. Also to find out the difference in the impact of covid-19 on global halal tourism and the halal hotel industry and whether Covid-19 is the end of halal tourism and hospitality as we know it or not. As well as providing guidance on how to deal with different aspects.Keywords: Halal Tourism, Mandailing Natal Is Hampered Due , COVID-19 Pandemic